Correlation of Microvessel Density with Clinicothological Features of Hodgkin Lymphoma - Bima Zulfikar, M.; Murti, Krisna; Andriyani Liberty, Iche; Dewi, Citra; Sari Puspita Rasyid, Riana (Majalah Patologi Indonesia, 2023)
BackgroundAngiogenesis is the process of new blood vessel growth that has an important role in tumor development. Microvessel density (MVD) assessment is one of the methods to assess angiogenesis. A high MVD is associated with a poor prognosis in various types of cancer including Hodgkin lymphoma (HL). Although, HL incidence is lower in developing countries, the death rate is higher in these regions. Moreover, this type of lymphoma is higher among young and reproductive people. The aim of this study was to determine the association between microvessel density and HL clinicopathological characteristics.MethodsThis was an observational analytic study with a cross-sectional method, conducted at the Anatomical Pathology Department/Dr. Mohammad Hoesin Palembang. The samples were paraffin blocks diagnosed as HL for period 2016-2021 and had complete clinicopathological data according to the criteria of this study. The slides were immunostained with antibody anti-CD34. One microvessel was determined by observing the endothelial morphology and CD34 expression in endothelial cytoplasm and/or cell membrane, then was evaluated and calculated by Image J. Data was statistically analyzed by STATA version 15.ResultsMajority HLs in this study were discovered in the age group of <45 years (71.00%), male (61.30%), nodal location (80.60%) and lymphocyte rich classical HL (LRCHL) subtype (51.60%). Although there was no significant association between MVD and the clinicopathological characteristics of HL, high MVD tend to occur in the age <45 years, male, nodal location, and LRCHL subtype.ConclusionThere was no significant association between microvessel density and HL clinicopathological characteristics.